Sensitivity analysis of rapid antigen tests for the Omicron SARS-CoV-2 variant detection from nasopharyngeal swab samples collected in Santiago of Chile - Carlos Barrera-Avalos; Javier Mena; Roberto Luraschi; Patricio Rojas; Carlos Mateluna-Flores; Eva Vallejos-Vidal; Mónica Imarai; Mónica Imarai; Ana María Sandino; Ana María Sandino; Daniel Valdés; Daniel Valdés; et al. (Frontiers Media S.A., 2022)
The COVID-19 pandemic continues to be a concern and keeps global health authorities on alert. The RT-PCR technique has been the gold-standard assay for detecting the SARS-CoV-2 virus. However, rapid antigen tests (RATs) have been widely used to increase the number of tests faster and more efficiently in the population. Nevertheless, the appearance of new viral variants, with genomic mutations associated with greater contagiousness and immune evasion, highlights the need to evaluate the sensitivity of these RATs. This report evaluates the sensitivity of SD Biosensor-Roche, Panbio™, and Clinitest® RATs widely used in Santiago de Chile in the detection of the Omicron variant from Nasopharyngeal samples (NPSs), the most predominant SARS-CoV-2 variant in Chile and the world. SD Biosensor-Roche shows a detection sensitivity of 95.7% in the viral amplification range of 20 ≤ Cq < 25, while Panbio™ and Clinitest® show 100% and 91.3%, respectively. In the viral amplification ranges of 25 ≤ Cq < 30, the detection sensitivity decreased to 28% for SD Biosensor-Roche, 32% for Panbio™, and 72% for Clinitest®. This study indicates that the tested RATs have high sensitivity in detecting the Omicron variant of concern (VOC) at high viral loads. By contrast, its sensitivity decreases at low viral loads. Therefore, it is suggested to limit the use of RATs as an active search method, considering that infections in patients are increasingly associated with lower viral loads of SARS-CoV-2. These antecedents could prevent contagion outbreaks and reduce the underestimation of the current Omicron variant circulation at the local level.